Hydrological modeling of the urban basin of the Bélico river in the city of Santa Clara, Cuba - Castillo García, Carlos Lázaro; Carvajal González, Victor Manuel (Enfoque UTE, 2023)
Urban floods are a phenomenon associated with heavy rainfall in relatively short periods of time, the causes that cause them are dissimilar and are generally accompanied by poor urban planning that reduces hydraulic sections of rivers, streams, and any drainage channel. The city of Santa Clara in Cuba, presents serious flooding problems near the Bélico and Cubanicay rivers due to the decrease in the section of their channels due to urban indiscipline. This contribution obtains the values of the maximum runoff flow for various control sections located along these rivers, using the TR-55 model (Technical Report 55) of the United States Natural Resources Conservation Service (NRCS), for its acronym in English, formerly named Soil Conservation Service). Three models associated with convective rains Type I, II, III, associated with the peaks of the storms and their temporal location will be carried out, with which the maximum expenses associated with storms of different configuration can be defined for a probability of 1%, 2% and 10%. The results obtained show that the most critical situation occurs for Type III rain and the maximum runoff value for a 1% probability at the basin closure point is 170 m3/s.